Disease of poultry - Barnes, H. John; Saif, Y. M. (Ames, Iowa : Blackwell Publishing, 2008)
Now in its Twelfth Edition, Diseases of Poultry continues its tradition of excellence as the definitive reference of poultry disease. Following the same user-friendly format, the book has been thoroughly updated to reflect the most current knowledge of avian pathology, including new coverage of genetic resistance to disease
1. Section I: Viral diseases -- 2. Section II: Bacterial diseases -- 3. Section III: Fungal diseases -- 4. Section IV: Parasitic diseases -- 5. Section V: Noninfectious diseases -- 6. Section VI: Other diseases
Includes bibliographical references and index
Keywords: Poultry -- Diseases